Japanese diplomacy : the role of leadership - Envall, H. D. P. (SUNY series, James N. Rosenau series in global politics., 2015)
Groundbreaking study demonstrating how Japan's leaders play an important role in diplomacy. A political leader is most often a nation's most high-profile foreign policy figure, its chief diplomat. But how do individual leadership styles, personalities, perceptions, or beliefs shape diplomacy? In Japanese Diplomacy, the question of what role leadership plays in diplomacy is applied to Japan, a country where the individual is often viewed as being at the mercy of the group and where prime ministers have been largely thought of as reactive and weak. In challenging earlier, simplified ideas of Japanese political leadership, H. D. P. Envall argues that Japan's leaders, from early Cold War figures such as Yoshida Shigeru to the charismatic and innovative Koizumi Jun'ichirō to the present leadership of Abe Shinzō, have pursued leadership strategies of varying coherence and rationality, often independent of their political environment. He also finds that different Japanese leaders have shaped Japanese diplomacy in some important and underappreciated ways. In certain environments, individual difference has played a significant role in determining Japan's diplomacy, both in terms of the country's strategic identity and summit diplomacy. What emerges from Japanese Diplomacy, therefore, is a more nuanced overall picture of Japanese leadership in foreign affairs.